Studi tentang Pengelolaan Kesan Elite Lokal Umaro terhadap Jawara dan Ulama di Banten Selatan - Karomani karomani (MediaTor (Jurnal Komunikasi), 2008)
Umaro, ulama and jawara in Menes Banten are local elites, who have important roles and influence in the society. The umaro has a strong influence in the network power of governance, the ulama has a strong influence in the field of religion, and the jawara has a strong influence in the field of culture and traditional customs. This research was conducted using qualitative approach to the elite of umaro, jawara, and ulama. Data is obtained from informants who played the role of umaro, jawara and ulama in the district of Menes Banten by using circumstantial interview, involves observation and document study. Data analysis used a qualitative method pattern. Research result indicated that communication umaro elites towards jawara and ulama couldnot be avoided from management of impression, verbally or nonverball.